State Authorities’ Powers to Determine the Budget Deficit and Public Debt in the Light of the Articles of the Constitution and the Law of the European Union - Andrzej Borodo (Prawo Budżetowe Państwa i Samorządu)
The issues of public debt and budget deficit are regulated by constitutions (e.g. of Poland, Germany, Spain) as well as by the law of the European Union. The constitutional regulations concerning public debt and deficit are norms primarily directed at governments and parliaments. However, these regulations mainly have a preventive and auxiliary character and cannot by themselves stop the debt level of the state from increasing. Financial aims concerning debt and deficit can be achieved by non-financial methods, i.e. through the appropriate social and economic policies implemented by the authorities enjoying considerable social respect. The EU regulations regarding public debt and deficit can only be implemented with the instruments of the national law. The set of the EU regulations limiting the budgetary powers of member states, including the budgetary powers of governments and national parliaments, are questionable and undermine the authority of the state.